Building Democratic Character Education through Cooperative Learning Based on Concept Mapping - Latifah, Elisah Novi; Suradji, Muchamad; Munif, Moh. Vito Miftahul (Universitas Al-Amien Prenduan, 2025)
A crucial component of education, particularly in madrasahs, is fostering political spirit. By using the paradigm, this study seeks to characterize democratic character education. Class XI MA Matholi'ul Anwar's Islamic Cultural History (SKI) course uses concept mapping as the foundation for cooperative learning.This study employs a descriptive design, an instrumental case study type, and a qualitative methodology. Participant observation, semi-structured interviews, and documentation were used to gather data from 30 students who were purposefully chosen as subjects and SKI teachers. The study's findings demonstrated that using this strategy produced participative, cooperative, and active learning. The attitudes of tolerance, consideration, accountability, and respect for one another all increased among the students. Therefore, the Concept Mapping-based Cooperative Learning paradigm works well in. Thus, the model Cooperative Learning based on Concept Mapping is effective in forming students' democratic character through meaningful and enjoyable learning.